Marginal voices : studies in converso literature of Medieval and Golden Age Spain - Aronson-Friedman, Amy; Kaplan, Gregory B., 1966- (Medieval and early modern Iberian world, 2012)
This collection of essays reveals the diversity of the impact on late medieval and Golden Age Spanish literature of the socio-religious dichotomy that came to exist between conversos (New Christians), who were perceived as inferior because of their Jewish descent, and Old Christians, who asserted the superiority of their pure Christian lineage.